MOTIVASI RUSIA MENGANEKSASI SEMENANJUNG KRIMEA TAHUN 2014 - Devindra Oktaviano Ramkas; Yuli Fachri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes Russia’s motivation on taking Crimea Peninsula byforce from Ukraine in March 2014 or internationally called as CrimeaAnnexation. After Ukraine’s Euromaidan Revolution ended in february 2014with the escape of President Viktor Yanukovych to Russia and the interimgovernment was formed, a new separatist conflict arise in the regions thatpredominantly Russian speakers and led by the Crimea secession which wasfollowed soon by Russia’s annexation. Russia has been violated manyinternational agreements and bring it to the condemnation by internationalcommunity and western countries were planned to impose sanctions. Thiscase will be analyzed within the framework of offensive realism with securityapproach. Under the assumptions of the thories, security dilemma andoffensive capabilities lead to the expansion by great powers, mainly territorialexpansion. Russia seeking to strengthening political influence and security inthe Black Sea Region, where Crimea, Ukraine, and Russia are located.Security dilemma comes from political and military expansion by NATO,European Union, and United States. Annexation of Crimea showed thatRussia has returned to a great power and the rivalry between Westerncountries and Russia actually continues even though cold war has ended morethan two decades ago.Keywords: Annexation, Black Sea Region, European Union, Territorial Expansion,NATO, Offensive Realism, Russia, Security